Influences of Multisensory Experience on Subsequent Unisensory Processing - Shams, Ladan; Wozny, David R.; Kim, Robyn S.; Seitz, Aaron (Frontiers in Psychology, 2011)
Multisensory perception has been the focus of intense research in recent years. It is now well established that crossmodal interactions are ubiquitous in perceptual processing and endow the system with improved precision, accuracy, processing speed, etc. While these findings have shed much light on principles and mechanisms of perception, ultimately it is not very surprising that multiple sources of information provide benefits in performance compared to a single source of information.Here, we argue that the more surprising recent findings are those showing that multisensory experience also influences the subsequent unisensory processing. For example, exposure to auditory-visual stimuli, can change the way auditory or visual stimuli are processed subsequently even in isolation. We review three sets of findings that represent three different types of learning ranging from perceptual learning, to sensory recalibration, to associative learning. In all these cases exposure to multisensory stimuli profoundly influences the subsequent unisensory processing. This diversity of phenomena may suggest that continuous modification of unisensory representations by multisensory relationships may be a general learning strategy used by the brain.